Influences on Islam-related news content : media experts perspectives - Isyaku Hassan; Mohd Nazri Latiff Azmi; Abubakar, Usman Ibrahim; Nasidi, Qaribu Yahaya; Shehu, Abubakar (Penerbit Universiti Kebangsaan Malaysia, 2021)
Islam is often portrayed negatively through manipulation of news content. Thus, a growing number of scholars have expressed concern over how Islam-related news is constructed. Therefore, this study aims to address the question of what influences Islam-related news content from the media experts’ perspectives. The study employed a qualitative approach in which interviews were used as a data-gathering instrument. The participants consist of experts in the field of media and communication. Altogether, six experts were selected based on their intellectual ability and willingness to respond to the interview questions. The interview data were analyzed using inductive thematic analysis. The findings revealed that journalists’ prejudices, inadequate training, as well as media ownership are critical in the process of Islam-related news formation. These influences represent a serious problem that constitutes an obstacle to a good reporting of religion. It was envisaged that this study would be useful to journalists, media owners, governments, media policymakers, and other responsible bodies particularly in the process of news gathering, production, and dissemination. This study could also advance our understanding of the complex factors shaping Islam-related news content.